A STUDY OF THE MEDIAN RUN LENGTH (MRL) PERFORMANCE OF THE EWMA t CHART FOR THE MEAN - Chin, W. S.; Khoo, M. B. C. (South African Journal of Industrial Engineering, 2012)
The exponentially weighted moving average (EWMA) chart is effective in detecting small shifts. However, the EWMA chart is not robust enough to prevent errors in estimating the process standard deviation or a changing standard deviation. To overcome this problem, Zhang et al. suggested the EWMA t chart in 2009. The existing optimal design of the EWMA t chart is based on the average run length (ARL) criterion. This paper proposes that the optimal design of the EWMA t chart be based on the median run length (MRL). The MRL performances of the optimal EWMA and optimal EWMA t charts are compared.